Legal Certainty of Telemedicine Provision in Technology-Based Health Services in Indonesia - Hadi Zulkarnain; Azis Budianto (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Technological advances in healthcare, particularly the use of Information and Communication Technology (ICT), have led to the emergence of telemedicine, which provides remote medical and health services. This innovation has the potential to revolutionize healthcare delivery but also presents legal challenges related to its legitimacy and the protection of patient data. In Indonesia, the legal framework for telemedicine is still developing, raising questions about its legal certainty and compliance with regulations. Purpose. This study aims to analyze the legal certainty surrounding the implementation of telemedicine in technology-based health services in Indonesia, focusing on its regulatory framework and the legal protection of patient data. Method. This is a normative legal study using secondary data, analyzed descriptively. The study examines existing regulations, government policies, and case studies of telemedicine platforms in Indonesia to assess the legal status of telemedicine services. Results. The study finds that the legal certainty of telemedicine in Indonesia is not fully realized. While the theory of utilizing ICT in healthcare, such as telemedicine, is supported, practical implementation remains incomplete. Telemedicine services like Alodokter and HAlodokter exist, but their legal foundation is still lacking. The Government Regulation concerning telemedicine, mandated by Article 25, Section (5) of Law No. 17/2023 on Wellbeing, has not been issued, leaving gaps in the legal framework. Conclusion. The legal framework for telemedicine in Indonesia requires immediate development. A Government Regulation must be issued to address key issues such as business licensing, electronic signatures, doctor identity verification, and the rights and obligations of doctors and patients. This regulation will ensure that telemedicine services operate within a clear and legally secure framework.